Sedimentological and GPR Studies of Subglacial Deposits in the Joux Valley (Vaud, Switzerland): Backset Accretion in an Esker Followed by an Erosive Jökulhlaup - Fiore, Julien; Pugin, André; Beres, Milan (Géographie physique et Quaternaire, 2002)
AbstractDuring the Würmian glaciation, the Jura ice sheet covered the Joux Valley (Vaud, Switzerland). A geomorphological study reveals many drumlins in this valley. Some are composed of gravels and sand, others of till. Outcrops show that the surface of the sandy-gravel drumlins is a major and sharp erosion surface. Given the lack of shearing structures in sediments below this erosion level, its origin cannot be linked to ice action of the glacier. Very high-energy subglacial meltwater floods (jökulhlaups), probably due to the drainage of subglacial or supra-glacial lakes, are the more likely cause of the erosion. Results of a ground penetrating radar (GPR) survey show the internal structure of one of these sandy-gravel drumlins to depth of 15 m. These GPR data, together with sedimentological observations, indicate that prior to erosion, subglacial sedimentation occurred in closed conduits (eskers) with strong and rapid flow variations. The sediments contain large chute-and-pool structures (high flow energy backset accretion) with dimensions comparable to the conduit width. Therefore, we interpret these sandy-gravel drumlins as portions of eskers, their present drumlin shape being the result of erosion by one or many jökulhlaups.The good preservation of the subglacial meltwater deposits is the result of the closed-basin geometry of the Joux Valley, which limited movement at the base of the glacier. This new contribution to the interpretation of the Joux Valley glacial features underlines the importance of meltwater in sedimentological processes under the Jura ice sheet.